2016
DOI: 10.1002/aic.15240
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐scale analysis of acoustic emission signals in dense‐phase pneumatic conveying of pulverized coal at high pressure

Abstract: in Wiley Online Library (wileyonlinelibrary.com) Acoustic emission technique in conjunction with multiscale processing method has been utilized to investigate the flow behavior of the dense-phase pneumatic conveying system at high pressure. A clearly defined classification of microscale, mesoscale, and macroscale signals has been put forward with the aid of wavelet transform and V statistics analysis. The detailed signals d 1 -d 4 , d 5 -d 7 , d 8 -d 10 were recomposed into the microscale, mesoscale, and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 42 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…He et al found that in the pneumatic conveying process, frequency analysis of acoustic signals generated by particle‐wall contacts could be further used to characterize the particle conveying behaviors from a microscopic perspective. Using db2 wavelet function to decompose the original signal (900 kHz) by 10‐scales wavelet transform, signals with different frequency ranges can be obtained and the energy fraction of each scale stands for the percentage of signals located in this frequency range.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…He et al found that in the pneumatic conveying process, frequency analysis of acoustic signals generated by particle‐wall contacts could be further used to characterize the particle conveying behaviors from a microscopic perspective. Using db2 wavelet function to decompose the original signal (900 kHz) by 10‐scales wavelet transform, signals with different frequency ranges can be obtained and the energy fraction of each scale stands for the percentage of signals located in this frequency range.…”
Section: Resultsmentioning
confidence: 99%
“…According to He et al, acoustic energies in different scales were generated by different kinds of particle‐wall contact patterns. Collision signals generated by vertical particle‐wall contacts were mainly distributed in the d 1 ‐d 3 scales, while friction signals generated by parallel particle‐wall contacts mainly located in the d 4 ‐d 5 scales.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations